2020
DOI: 10.1111/cpr.12828
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomal microRNAs in lung cancer biology and clinical applications

Abstract: Lung cancer is the second most common and the most lethal cancer worldwide, accounting for 11.6% of all new cancer cases and 19.8% of all cancer-related deaths. 1 Recent research has fostered new insights into lung cancer biology, and considerable progress has been made in the field of novel biomarker-targeted therapies, including molecular therapies targeting epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK) and proto-oncogene B-Raf (BRAF), 2,3 and immunotherapies with checkpoint inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 78 publications
0
71
0
1
Order By: Relevance
“…42 For exosomal miRNAs in lung cancer research, Hu et al summarized the exosomal miRNAs in lung cancer as the diagnostic, predictive and prognostic biomarkers. 43 Exosomes isolated from the plasma of 45 non-small cell lung cancer patients and 31 controls were analyzed and indicated that exosomal miR-126 was upregulated and could be the diagnostic biomarker for non-small cell lung cancer. 44 Elevated levels of circulating exosomal miR-23a are found in the sera of lung cancer patients, and miR-23a levels are positively correlated with proangiogenic activities, which could also be used as a biomarker for the diagnosis of lung cancer.…”
Section: Contents Of Exosomesmentioning
confidence: 99%
“…42 For exosomal miRNAs in lung cancer research, Hu et al summarized the exosomal miRNAs in lung cancer as the diagnostic, predictive and prognostic biomarkers. 43 Exosomes isolated from the plasma of 45 non-small cell lung cancer patients and 31 controls were analyzed and indicated that exosomal miR-126 was upregulated and could be the diagnostic biomarker for non-small cell lung cancer. 44 Elevated levels of circulating exosomal miR-23a are found in the sera of lung cancer patients, and miR-23a levels are positively correlated with proangiogenic activities, which could also be used as a biomarker for the diagnosis of lung cancer.…”
Section: Contents Of Exosomesmentioning
confidence: 99%
“…It has been demonstrated that cancer-secreted exosomal miRNAs could be horizontally transferred to the target cells, thereby controlling the biology of cancer cells. 22 For example, exosomal miR-208a from A549 cells, through targeting p21, restrained the proliferation of NSCLC cells via activating the AKT/mechanistic target of rapamycin signaling. 23 Similarly, exos derived from the gemcitabine-resistant A549 cells transferred miR-222-3p to A549 cells and then promoted the proliferation, migration, and invasion of A549 cells by targeting suppressor of cytokine signaling 3.…”
mentioning
confidence: 99%
“…This process is sustained by EVs via delivery and release of their targets into a target cell(s). Alongside tumor progression, EVs have the capability of carrying out other critical processes, including cell proliferation, tumor growth [ 76 ], angiogenesis [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], matrix remodeling, metastasis [ 75 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ], immune escape [ 69 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ], resistance to apoptosis [ 110 , 111 , 112 , 113 ], deregulation of energetic metabolism [ 114 , 115 , 116 , 117 ], sustaining proliferative signaling [ 94 , 118 , 119 , 120 ], evading growth suppression [ 121 , 122 , 123 ], deregulating and tumor-promoting inflammation [ 100 , 124 , ...…”
Section: Pathological Roles Of Evsmentioning
confidence: 99%